ANALISIS KEPUTUSAN KONSUMEN TERHADAP KOSMETIK HALAL PADA APLIKASI TIKTOK SHOP PENDEKATAN THEORY OF PLANNED BEHAVIOUR: (STUDI PADA MASYARAKAT PAMEKASAN) - Alifah Alifah; Nuri Herachwati; Ridan Muhtadi (LP2M IAI Miftahul Ulum Pamekasan, 2022)
This study aims to determine and empirically test consumer decisions regarding halal cosmetics on the Tiktok Shop application in the Pamekasan community. The global Muslim population reached 1.9 billion in 2019 and is expected to double to 3 billion by 2060. This development is predicted to increase 70% from the 2015 population and will represent 31.1% of the global population. The rapid development of the population is in line with the increasing demand for halal-based products. The development of technology and the all-digital era has an impact on people's lifestyles. One of them is having an application that is easy to manage and use. Applications can provide a hub to support users. One example of an application that is currently popular among the public is the Tiktok application. This study uses quantitative methods using the concept of Extended Theory of Planned Behavior (TPB) theory with halal literacy variables as moderation processed through